Indonesiaâ€™s Way To Counter Terrorism 2002â€”2009: Lesson Learned - MUHAMMAD, ALI (Universitas Muhammadiyah Yogyakarta, 2014)
Terrorism emerged as serious security problem inIndonesia since a network of terrorist group rockedthis country, started from the Bali bombing (2002)followed by other consecutive bombings, such as, J.W. Marriott Hotel bombing (2003), the AustralianEmbassy bombing (2004), and the Ritz Carlton Hotelbombing (2009). This article attempts to examinethe ways in which the government responded towardsthe problem. What sort of policies did theIndonesian government take to respond to terrorismduring the 2002â€”2009 period? This study uses aqualitative research method. The data used in thisresearch are derived from official documents, directinterviews with government officials and the secondarysources (books and journals) on terrorism andcounterterrorism. This article shows that the governmentadopted the legal approach or law-enforcement(â€œhard approachâ€) by issuing the anti-terrorismlaw as a legal framework and by reorganizingthe police force to strengthen its counter-terroristcapability. It also adopted an â€œideologicalâ€ approach(soft approach) to battle religious extremism. Thissort of approach is mainly aimed at defusing andneutralizing the religious extremism of terrorist groupsand preventing it from spreading into the wider community.This article shows that the government hasused effectively both approaches in destroying problemof terrorism in Indonesia.Key Words: Indonesia, policy, terrorism,counterterrorism, legal approach, â€œideologicalâ€approach.